Implementation of Zakat Fund Utilization Management to Asnaf Fi Sabilillah (Case Study of LAZ Al Bunyan) - Ningrum, Tri Ambar; Hamdani, Ikhwan; Hakim, Nurman (Al-Infaq: Jurnal Ekonomi Islam, 2023)
Management is needed for Zakat Management Institutions in the process of collecting, distributing and utilizing zakat funds. One of the amil zakat institutions in the city of Bogor on a scale of West Java Province is LAZ Al Bunyan. LAZ Al Bunyan already has a management system for the utilization of zakat for asnaf fi sabilillah as well as forming a zakat fund utilization program as an effort to utilize zakat funds for asnaf fi sabilillah. This study aims to explain how the management and efforts in utilizing zakat to asnaf fi sabilillah are carried out by LAZ Al Bunyan. In this study, the authors used a qualitative research method with a descriptive approach. Data collection techniques include observation, interviews, and documentation. The results of this study are that LAZ Al Bunyan has implemented management functions in the utilization of zakat to asnaf fi sabilillah, namely planning, organizing, actuating, and controlling. The form ofutilization efforts carried out on asnaf fi sabilillah is the establishment of the Indonesian House program which includes the dimensions of maqashid sharia as well as a special program of utilization for asnaf fi sabilillah based on Islamic boarding schools, namely the "Pesantrenku Jalan Surgaku" program.